Políticas de inclusión en la universidad argentina: El caso de las becas y el bienestar estudiantil en la Universidad Nacional de San Martín - Arias, María Fernanda; Lastra, Karina (Universidad de Costa Rica, 2019)
The article aims to analyze the progress and difficulties in the implementation of institutional policies aimed at favoring inclusion in the National University of San Martin (Argentina). The same is an advance on the study of democratization in the aforementioned University in which it is about knowing the policies that facilitate the opening of the university to lower income sectors. This university is located in the Buenos Aires Conurbation, a territory characterized by high levels of poverty, which faces problems of desertion and low academic performance. Although the work is part of a broader line of research, this article, after a historical-political contextualization at the global, regional and national level on the real validity of the right to Higher Education, stops at the Scholarship policies, Student Well-being, University Pedagogy and Mentoring. The objective of the study, in process, is to characterize, relieve and systematize the institutional policies and specific programs related to these areas. It is an exploratory study; The design and methodology of research has been inscribed in a mainly qualitative logic. Two different registers were used for the construction of empirical evidence, one, through the documentary analysis of various secondary sources; the other, based on semi-structured interviews with authorities and coordinators. Based on the data presented, it is concluded that although institutional policies and specific programs are being developed to encourage the retention, permanence and graduation of students in vulnerable situations, it is necessary to continue investigating and evaluating their real effectiveness and fundamentally securing resources for their sustainability and expansion of coverage. It is noted that it is worrisome that the current university budget shows sub-execution in sensitive areas such as university welfare programs.